Síndrome de Burnout en cirujanos dentistas.: Burnout syndrome in dentists. - Pinella Vega, Melissa (2022)
A scientific assay is presented, the objective of this is to provide the state of the art on Burnout Syndrome in dentists. And its purpose is to recognize a syndrome as a predisposing factor that deteriorates the exercise of professional practice and that could lead to negative consequences for the health of dental professionals.